John Forrester (1949-2015): a historian of psychoanalysis - León, Ramón (2023)
John Forrester (1949-2015) was a British scholar who dedicated his work to the history of the Freudian doctrine and the evolution of the psychoanalytic movement. His first book, Language and the Origins of Psychoanalysis (1980), analyzes the role of words in Sigmund Freud's theory and therapy. His last work, Freud in Cambridge (2017), written with L. Cameron, is a detailed study of the reception and evolution of psychoanalysis in England. Forrester also translated Jacques Lacan’s seminars into English, a major task considering the peculiarities of Lacan’s style. This communication briefly presents his biography and tries to assess his work.